Investigating of Subjective Well-being On the Honorary Education Staff at Malikussaleh University, Aceh - Safuwan Amin; Rahmia Dewi; Nur Afni Safarina (Department of Islamic Psychology, Institut Agama Islam Negeri Syaikh Abdurrahman Siddik Bangka Belitung, 2022)
This study presents the Subjective Well-being of honorary employees of education staff (tendik) at Malikussaleh University (Unimal). Subjective well-being (SWB) as a psychological construct is oriented to the individual's positive appraisal and affection towards the reality of his life journey. Work routines carried out by individuals are the main focus of arising out of SWB in individual reality because work is understood as a means of forming a decent (prosperous) life. The objectivity of this study explains the individual's knowledge of SWB, the meaning of SWB in the reality of work, and the factors that encourage the arises of SWB in individuals. The design of this study used a phenomenological type of qualitative approach. Participants were taken randomly through purposive sampling input, totaling 15 people from 25 planned research subjects. Field data searches were carried out by in-depth interviews and FGDs. The findings of this study inform that in general, honorary education staff working at Unimal have good SWB, even though they are still honorary staff.